Functional use of Shengjin Hu National Nature Reserve, China, by three species of dabbling ducks preliminary observations - Dou, Song Tao; Cao, Lei; Cheng, Yuan Qi; Fox, Anthony D (Wildfowl, 2013)
Counts made at Shengjin Lake, China, in 2008/09 found internationally important numbers of Falcated Duck Anas falcata and nationally important numbers of Baikal Teal Anas formosa wintering at the site. Activity budgets showed that neither species fed at all during daylight hours in February, but that the large raft of ducks took to the air at dusk and flew to harvested rice fields to feed at night. Baikal Teal had departed the site by early April, whereas Falcated Duck activity budgets at this time showed the species remaining to forage in a series of feeding/loafing cycles on the lake during the day, having abandoned night-time feeding in the fields. In contrast, the more common and widespread Spot-billed Duck Anas poecilorhyncha, which also winters in the area, remained to feed on the lake throughout the day, although the possibility remains that they may also feed in fields if they leave the lake after dark. These findings confirm that the globally threatened Falcated Duck and globally vulnerable Baikal Teal derive a major part of their energy and nutrition from agricultural fields at Shengjin Lake National Nature Reserve in mid-winter, potentially putting them at risk of land-use change and pesticides in the vicinity. On the other hand, the gleaning of waste unharvested grain creates no agricultural conflict and offers opportunities for developing management agreements with farmers, which would provide a feeding resource for maintaining and enhancing stocks of these ducks wintering at the site.